Analyzing decisiveness of migration intentions: Social kinship that matters - Aubrey D. Tabuga (Philippine Institute for Development Studies (PIDS), 2018)
Analyzing future migration intentions is essential in understanding how migration is perpetuated. International migration is such a complex and nuanced phenomenon that those who desire to participate in it go through an elaborate process of intention-formation, planning and decision-making. And yet the literature on migration intentions rarely view it in such manner. Instead, many studies treat migration decision-making as a binary stay-or-leave variable. Moreover, the lens more commonly implemented is economic; there is less focus on the social dimensions of migration decisions. This analysis seeks to explain the influence of social networks on the decisiveness to migrate while controlling for the effects of economic forces, subjective perceptions on well-being, and demographic factors. Using information gathered from individuals residing within a village with high migration incidence, this study found that differentiating migrant networks into degree of association or strength of ties is crucial because different networks have different effects. For intention formation, it is the most immediate, closest of all migrant networks (i.e. intra-household networks) which enhance the decisiveness; migrant networks beyond one's own household are either insignificant or negatively related to intention formation. This paper therefore argues that using aggregate measures like migration incidence in an area wherein homogeneity is assumed and obtaining a significant and positive effect may erroneously amplify the power of migration network in the perpetuation of migration activities. Furthermore, the key to understand the process is to take into account the differences in individuals' phases of migration decision-making in the analysis of factors that influence the decisions. Indeed, network effects vary depending on where one is in the decision-making process. Migrant networks particularly the closest of kin are important in the advanced phase of concrete migration planning, and not in the initial stage. This is an evidence that migrant networks are not only important sources of migration-related information and aspirations but also sources of financial support or the money to move.
Keywords: 330; Migration intention; migration decision-making; Philippine migration; generalized ordered logit; tie strength